Analisis Perhitungan Pemotongan Pajak Penghasilan (PPH 21) Atas Penambahan Upah Lembur Dan Penentuan Bonus Menggunakan Metode Topsis Guna Menentukan Take Home Pay Karyawan - Luzy Nur Agustin; Marhaendra Kusuma; Muhammad Alfa Niam; Ahmad Yani (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
PT. xxx is a company that operates in the business of processing wood in the form of logs into layers that are ready to be marketed. The purpose of this research is to determine employee Take Home Pay after receiving incidental income in the form of overtime pay and bonuses. The sampling technique in this research used the Non-Probability Sampling technique. Data collection was carried out using interviews and documentation methods.The research results show that determining bonuses using the TOPSIS method is different from before the TOPSIS method was used. With this, the Take Home Pay that employees receive before implementing TOPSIS is very different from after implementing the TOPSIS method.